2014
DOI: 10.1089/nat.2013.0449
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splice Forms of CTLA-4 Induced by Antisense Mediated Splice-Switching Influences Autoimmune Diabetes Susceptibility in NOD Mice

Abstract: Activated and regulatory T cells express the negative co-stimulatory molecule cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) that binds B7 on antigen-presenting cells to mediate cellular responses. Single nucleotide polymorphisms in the CTLA-4 gene have been found to affect alternative splicing and are linked to autoimmune disease susceptibility or resistance. Increased expression of a soluble splice form (sCTLA-4), lacking the transmembrane domain encoded by exon 3, has been shown to accelerate autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Studies in NOD mice and other models have shown that differential expression of CTLA-4 splice variants impacts on T cell function and the overall immune response. Thus, while splice variants lacking the transmembrane domain exacerbate the autoimmune pathology, variants lacking the ligand-binding domain are protective (83, 84, 85). Importantly, AS is more frequent in the critical MHC region (a region that accumulates more than 40% of the genetic risk associated with T1D (86)) than it is genome wide (87).…”
Section: β Cell Death In Type 1 Diabetes and The Role Of Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in NOD mice and other models have shown that differential expression of CTLA-4 splice variants impacts on T cell function and the overall immune response. Thus, while splice variants lacking the transmembrane domain exacerbate the autoimmune pathology, variants lacking the ligand-binding domain are protective (83, 84, 85). Importantly, AS is more frequent in the critical MHC region (a region that accumulates more than 40% of the genetic risk associated with T1D (86)) than it is genome wide (87).…”
Section: β Cell Death In Type 1 Diabetes and The Role Of Asmentioning
confidence: 99%
“…The identification of splice variants acting as β cell autoantigens, modulators of immune response or β cell survival, may lead to the development of novel therapeutic strategies for T1D based on splicing modulation. In line with this possibility, the use of an AON-targeted splice-switching approach against the CTLA-4 gene, which modulates T cell activation and proliferation, reduced the incidence of insulitis and diabetes in diabetes-prone NOD mice (84). Another potential therapeutic target to enhance β cell survival is the short isoform of the pro-apoptotic BH3-protein Bim (Bim S).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Indeed, high serum levels of soluble CTLA-4 have been reported in type-1 diabetes patients [47]. Over expression of soluble CTLA-4 in mice can lead to the induction and exacerbation diabetes [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Isoforms of this protein are generated by AS due to the presence of a single nucleotide polymorphism. This gives rise to the normal full length protein and a shorter soluble sCTLA4 that lacks the transmembrane domain encoded by exon 4 (Gerold et al 2011, Mourich et al 2014. Another isoform is the result of the absence of the ligand binding domain encoded by exon 2 and is called liCTLA-4.…”
Section: Ctla-4mentioning
confidence: 99%
“…NOD mice have been used to study how these different isoforms can affect T cell response. NOD mice expressing the sCTL4 isoform are more prone to getting type 1 diabetes, while mice expressing liCTLA4 are more resistant to the getting the disease (Mourich et al 2014). This is due to the activation of the T cells as those lacking receptors with a ligand binding site showed reduced activity while the soluble CTLA4 has an increased ability to activate T cells.…”
Section: Ctla-4mentioning
confidence: 99%